2005
DOI: 10.1111/j.1601-0825.2005.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine digluconate induces mitotic recombination in diploid cells of Aspergillus nidulans

Abstract: Although, beneficial effects of chlorhexidine, as an antiseptic agent, are reported in the literature, our results revealed that chlorhexidine digluconate, at less levels lowered those used clinically, caused toxic and recombinogenic effects on diploid A. nidulans strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In these clinical situations, post-surgical control of the recipient graft area (root surface or extraction site) by an antimicrobial agent is recommended and widely used. With the goal to create an optimal environment for wound repair at the graft recipient site or implant placement site covered by rotated palatal flap, the excisional palatal wound is exposed to the antimicrobial agents, which display both bactericidal activity and potential cytotoxicity (Pucher & Daniel 1992, Kubert et al 1993, Mariotti & Rumpf 1999, Hidalgo & Dominguez 2001, Souza-Junior & Castro-Prado 2005.…”
mentioning
confidence: 99%
“…In these clinical situations, post-surgical control of the recipient graft area (root surface or extraction site) by an antimicrobial agent is recommended and widely used. With the goal to create an optimal environment for wound repair at the graft recipient site or implant placement site covered by rotated palatal flap, the excisional palatal wound is exposed to the antimicrobial agents, which display both bactericidal activity and potential cytotoxicity (Pucher & Daniel 1992, Kubert et al 1993, Mariotti & Rumpf 1999, Hidalgo & Dominguez 2001, Souza-Junior & Castro-Prado 2005.…”
mentioning
confidence: 99%
“…If such a mutagenic effect of CHX does exist, then antibiotic sensitivity could increase or decrease after CHX treatment. Based on a possible mutagenic effect and the resulting increased gene variation, as already shown by other authors [ 23 ], it can be assumed that the development of cross-resistance is promoted. However, resistance patterns for isolates of the untreated growth controls were also altered.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has not yet been clarified whether CHX possesses mutagenic effects, CHX was highlighted as being the only bisguanide that showed increased mutagenicity [ 22 ]. Furthermore, different studies have shown an increased mitotic crossing that is over-induced by the presence of CHX [ 23 ] and, in animal experiments, there were changes in cells from the blood and the kidneys after treatment with CHX [ 24 ]. Nevertheless, there are experiments showing that there is negative genotoxic potential CHX [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highest dose tested without a mutagenic effect was in the mouse dominant-lethal test 1000 mg/kg/d and in the cytogenetic test in the hamster 250 mg/kg/d [24]. With diploid cells of A. nidulans , a test model for the detection of carcinogenic agents, mitotic recombination were induced by 1.5 and 10 µM CHX (in the case of CHX corresponds to 0.0001343% and 0.00089577% respectively) [25]. An increase in chromosomal aberrations in the bone marrow was induced in the mouse following dermal application of 0.2 mL 0.5% CHx solution in distilled water twice daily for 28 days (50 mg/kg) [26].…”
Section: Discussionmentioning
confidence: 99%